What can functional Transcranial Doppler Ultrasonography tell us about spoken language understanding? - Badcock, N. A.; Groen, M. A. (Language, Cognition & Neuroscience, 2017)
This review describes language research conducted using the neurophysiological imaging technique, functional Transcranial Doppler Ultrasound (fTCD). FTCD estimates the blood flow velocity in the cerebral arteries from which, neural activity is inferred. The review provides a brief history and introduction to fTCD, including data acquisition, task design, and data processing. Challenges and solutions for the use of fTCD for language research are covered, reporting on production and comprehension paradigms, task difficulty and behavioural performance during covert and overt speech production, and participant characteristics (age and sex). We note the limited application of fTCD to the topic of spoken language understanding, commenting on the value of examining lateralisation in this endeavour, as well as the advantages of its use, namely portability and low cost, to supplement other imaging techniques.